Into the fire : a first-hand account of the most extraordinary battle in the Afghan War - Meyer, Dakota, 1988-; West, Francis J. (New York : Random House, 2012)
A Medal of Honor-awarded Marine sniper shares the controversy-marked story of his heroic contributions during a 2009 Taliban ambush during which he saved a company of Afghan soldiers and Marine advisors, a victory that compelled him to disobey orders and assume command without reinforcements or artillery support.
Along the Afghan-Pakistan border -- Finish the game -- The Marine years -- Monti -- Advising -- Coming together -- Out of the smoke -- Ganjigal -- Into the valley -- Paralysis -- Lost -- Into the fire -- Into the wash -- Primal -- Team Monti -- Dab Khar -- Cheerleaders -- Old haunts -- All in -- Epilogue / by Bing West.
Includes bibliographical references.
Keywords: Meyer, Dakota, -- 1988-; Meyer, Dakota, -- 1988-; United States. -- Marine Corps -- Officers; Ganjgal, Battle of, Ganjgal, Afghanistan, 2009.; Afghan War, 2001- -- Personal narratives, American; HISTORY -- Military -- Afghan War (2001- ); Afghanistan -- Kunar (Province); Afghan War, 2001-; 2009; Autobiography; Personal narratives; Personal narratives -- American; Personal narratives